Specific Recognition of p53 Tetramers by Peptides Derived from p53 Interacting Proteins - Gabizon, Ronen (Public Library of Science, 2012)
Oligomerization plays a major role in regulating the activity of many proteins, and in modulating their interactions. p53 is a homotetrameric transcription factor that has a pivotal role in tumor suppression. Its tetramerization domain is contained within its C-terminal domain, which is a site for numerous protein-protein interactions. Those can either depend on or regulate p53 oligomerization. Here we screened an array of peptides derived from proteins known to bind the tetrameric p53 C-terminal domain (p53CTD) and identified ten binding peptides. We quantitatively characterized their binding to p53CTD using fluorescence anisotropy. The peptides bound tetrameric p53CTD with micromolar affinities. Despite the high charge of the binding peptides, electrostatics contributed only mildly to the interactions. NMR studies indicated that the peptides bound p53CTD at defined sites. The most significant chemical shift deviations were observed for the peptides WS100B(81–92), which bound directly to the p53 tetramerization domain, and PKCα(281–295), which stabilized p53CTD in circular dichroism thermal denaturation studies. Using analytical ultracentrifugation, we found that several of the peptides bound preferentially to p53 tetramers. Our results indicate that the protein-protein interactions of p53 are dependent on the oligomerization state of p53. We conclude that peptides may be used to regulate the oligomerization of p53.